(untitled) (Experimental biology, 2016)
Sterilizing agents and their concentrations for the disinfection of explants from saprophyte microflora were identified, the composition of nutrient media was specified that is optimal for introduction of pear into in vitro culture and micropropagation. Explants should be effectively sterilized with one of antiseptics: a) HgCl2 0.1% in the exposure of 10-15 min; b) «Domestos» without dilution – 3 min. The content in MS medium with GA-0.5 mg/l, IBA-0.1 mg/l is optimal for the introduction of pear into in vitro culture. MS medium containing BAP-0.6 mg/l; IBA-0.1 mg/l; GA-0.2 mg/l; sucrose-30 g/l is optimal for propagation of pear explants in the in vitro culture.